Contribution of Fcγ receptor IIIA gene 158V/F polymorphism and copy number variation to the risk of ACPA-positive rheumatoid arthritis. Issue 11 (19th November 2008) - Thabet, M M; Huizinga, T W J; Marques, R B; Stoeken-Rijsbergen, G; Bakker, A M; Kurreeman, F A; White, S J; Toes, R E M; van der Helm-van Mil, A H M
Abstract : Background: Fcγ receptors (FcγRs) are potent immune modulators. FcγR genes encompass a complex region, polymorphic by both single nucleotide polymorphisms (SNPs) and copy number variation (CNV). The heterogeneity of rheumatoid arthritis (RA) combined with the genetic complexity of FcγR genes may be the cause of inconsistent findings in previous RA studies on FcγR SNPs. There is increasing evidence that anti-citrullinated peptide antibody (ACPA)-positive RA and ACPA-negative RA have a different genetic background. Objective: To investigate whether FcγRIIIA 158V/F SNP associates differently with ACPA-positive and ACPA-negative RA and to assess if the FcγRIIIA gene CNV affects the association of the FcγRIIIA 158V/F SNP with RA and whether the FcγRIIIA gene CNV confers risk for RA. Methods: 945 patients with RA and 388 healthy controls, all Dutch-Caucasians, were included in the study. FcγRIIIA 158V/F SNP was genotyped using Sequenom. CNV of the FcγRIIIA gene was determined in 456 patients with RA and 285 controls using multiplex ligation-dependent probe amplification. Associations between genotypes and RA were analysed, stratifying for the presence/absence of ACPA and CNV. Results: In all patients with RA the FcγRIIIA 158V/F SNP was not associated with RA. In ACPA-positive RA (n = 358), the VV genotype was more prevalent in cases than in controls (18.4% vs 13.2%, OR = 1.5, p = 0.05). After stratification for CNV the VV genotype was associated with RA in general (n = 426) (OR = 1.6, 95% CI 0.97 to 2.6, p = 0.05) and with ACPA-positive RA (n = 135) (OR = 2.1, 95% CI 1.2 to 3.8, p = 0.009) but not with ACPA-negative RA. The distribution of CNV was not significantly different between patients with RA and controls. Conclusion: The FcγRIIIA 158 VV genotype confers risk for ACPA-positive RA; this association increased slightly after correction for CNV of the FcγRIIIA gene. CNV itself is not associated with RA susceptibility.